Analysis of Psychological Capital and Social Capital on Innovative Work Behavior in Cirebon City and Regency Media Companies - Anggraeni, Citra; Fadilah, Alida Nur (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Optimizing all company resources is one way a company can survive with the times. Human resources are the main and most important part of creating and developing innovative ideas within the company. One aspect that causes change in a company is innovative work behavior, and the driving factors for creating innovative work behavior are psychological capital and social capital. So, this research aims to examine the relationship between psychological capital and social capital in innovative work behavior. Using quantitative research with employees of media companies in Cirebon City and Regency as the research population. Obtaining a sample of 153 respondents, using non-probability sampling techniques with questionnaire instruments and using multiple regression analysis on the SPSS 22 application. This research obtained results that there was a significant influence between Psychological Capital and Innovative Work Behavior, then there was a significant influence of Social Capital on Innovative Work Behavior, and the existence of a significant influence of Psychological Capital and Social Capital on Innovative Work Behavior.